Aktivitas Anticandida Herba Krokot (Portulaca grandiflora) - Agus Purwanto; Ch. Endang Purwaningsih; Christiana Indriasari (Florea : Jurnal Biologi dan Pembelajarannya, 2022)
The purslane plant has been designated by the World Health Organization as one of the most widely used medicinal plants in the world and is known as "Global Panacea". The diversity of purslane plants from the genus Portulaca amounts to about 40-100 species found in the tropics and in areas that have four seasons. Candidiasis is one of the most common fungal infections in humans. Candidiasis is an opportunistic infection caused by excessive growth of the genus Candida fungus, 70% of Candida infections are caused by Candida albicans. Research on the antifungal activity of the purslane plant P. grandiflora is still rarely done. This study aims to determine the effective dose of anticandidal activity of purslane herb (P. grandiflora) against the C. albicans test microbe. This research is an experimental study that includes in vitro biological testing with the disc diffusion method, namely testing the inhibition of the extract of P. grandiflora 20%, 40%, 60%, 80%, and 100% against the growth of the fungus C. albicans. The antifungal activity test was carried out by observing the diameter of the inhibition zone formed around the paper disk. Anti-candida activity test of purslane herb (P. grandiflora) magenta variety extract showed that there was a zone of inhibition that was significantly different between all treatment groups. The measurement of the inhibition zone in the treatment group with a concentration of 20 to 100%, respectively, was 6.33±20; 6.86±13; 7.59±21; 8.33±33; 9.66±21; 25.69±98, thus indicating a moderate inhibition category for the growth of C. albicans.